Preparation method of graphite magnesium silicate system conductive material

CN118684475BActive Publication Date: 2026-10-20UNIV OF SCI & TECH LIAONING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410397284.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2026-10-20
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

如申请号为CN202310374664.3中国专利提供了一种高强高导电性混凝土及其制备方法,所述导电混凝土加入了表面由掺杂了无机导电微粒的氢氧化铁包覆的改性钢纤维,使用碳载体、金属铜单质与铝酸三钙形成的混合体为导电填料,不仅使制备的导电混凝土兼具高强度和良好的导电性,而且克服了钢纤维在混凝土中的稳定性不足而造成混凝土的长期导电稳定性不足的问题

Benefits of technology

与现有技术相比,本发明的特点及其有益效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004774405320000071
    Figure BDA0004774405320000071
Patent Text Reader

Abstract

The application provides a preparation method of a graphite / magnesium silicate system conductive material. The graphite content in the magnesium silicate system exceeds the percolation threshold by adding a dispersant and separately calculating the water requirement for graphite dispersion, the preparation process is simple, efficient, environmentally friendly, and low in cost, the prepared graphite / magnesium silicate system conductive material is excellent in conductive performance and stable in structure, and still maintains good fluidity and strength when the graphite content is high. The preparation method comprises the following steps: dry mixing and stirring, preparing a dispersion solution, preparing a graphite dispersion solution, pulping, shaping, curing and the like, so that the graphite / magnesium silicate system conductive material at normal temperature is obtained, the graphite content of the obtained product is 30%, the strength retention coefficient is 0.49 when the resistivity is less than 1.37 ohm*cm, and the fluidity reaches 202 mm. The application has important significance for preparing a cement-based conductive material, improving the conductivity of magnesium silicate cement, and increasing the added value of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The main objective of this invention is to address the problems existing in the prior art by inventing a method for preparing conductive materials based on a magnesium silicate graphite system. Background Technology

[0002] Conductive cement is a special type of cement with higher electrical conductivity than ordinary cement, enabling it to conduct current to other materials. Its primary function is to conduct current, facilitating the transmission and distribution of electricity. It is essential for various applications, such as lightning protection and anti-static engineering in nuclear, thermal, and hydroelectric power plants, high-rise buildings, heat exchangers, drying rooms, non-icing airport runways, and shielding applications. In the future, conductive cement will be used in the construction industry for underfloor heating and antifreeze systems, using electric heating to keep the ground warm and dry, effectively ensuring the building's lifespan and comfort. In the power sector, it can be used in high-voltage cables and electromagnetic shielding to transmit power and protect equipment. Furthermore, its conductivity allows for anti-static applications, effectively preventing electrostatic interference. It also has broad application prospects in industrial automation and intelligent transportation. With the rapid development of high technology, new materials, and energy-saving and environmentally friendly technologies, the market demand for conductive cement will continue to expand, and its application scope and fields will be further broadened. Traditional cement has poor electrical conductivity, and conductive cement is generally produced by adding conductive admixtures to improve its conductivity. Currently, the admixtures used domestically and internationally for making conductive concrete are mainly graphite, carbon fiber and steel fiber, and conductive pearl powder. The overall dosage of conductive materials is relatively low, having little impact on resistance. However, excessive dosage can easily lead to overly thick cement and poor flowability. The manufacturing methods currently used for conductive cement are often quite cumbersome, resulting in poor conductivity, high cost, and limited practical value. Furthermore, limitations imposed by the type of cement often lead to problems such as severe segregation and clumping during mixing, excessive air content within the cement, unstable conductivity, poor water resistance, and low strength. To address the aforementioned issues, domestic enterprises have conducted extensive research. For example, Chinese patent application CN202310432735.0 proposes a self-compacting conductive concrete. This involves mixing HPMA dispersant, high-efficiency water-reducing agent, and water to form a solution, then adding it to limonite sand and stirring thoroughly. This solution, along with graphite, is then added to a mixture of ordinary silicate cement, grade I fly ash, and river sand. The mixture is stirred until homogeneous, then aggregate is added to the fine aggregate mixture. Finally, a mixture of the remaining water and defoamer is added and stirred until homogeneous. This process imparts conductivity to ordinary silicate concrete while enhancing its compactness. Another example is Chinese patent application CN201910026479.9, which proposes a conductive, ultra-high ductility cement-based composite material and its preparation method. Cement, fly ash, quartz sand, and nano-conductive carbon powder are dry-mixed, then water is added and wet-mixed to form a cement matrix. Carbon fibers and polyethylene fibers are then added and stirred evenly. After injection molding, demolding, and curing, the resulting conductive, ultra-high ductility cement-based composite material exhibits extremely high conductivity and crack control capabilities, making it suitable for road snow melting and de-icing. For example, Chinese patent application number CN201610085994.0 provides a conductive cement with internally incorporated low-melting-point alloys and its preparation method. In the provided conductive cement, the cement-based material and the conductive filler composed of low-melting-point alloys work synergistically in a reasonable ratio, resulting in good conductivity without significantly reducing strength, while avoiding the cost issues caused by the extensive use of fiber materials. For example, Chinese Patent Application No. CN202310374664.3 provides a high-strength, high-conductivity concrete and its preparation method. The conductive concrete incorporates modified steel fibers whose surface is coated with ferric hydroxide doped with inorganic conductive particles. A mixture of carbon carrier, elemental copper, and tricalcium aluminate is used as the conductive filler. This not only enables the prepared conductive concrete to have both high strength and good conductivity, but also overcomes the problem of insufficient long-term conductive stability of concrete caused by the insufficient stability of steel fibers in concrete. Existing conductive cements often suffer from poor conductivity, excessive air content, unstable conductivity, and poor water resistance. The manufacturing methods are also cumbersome, expensive, and environmentally unfriendly, limiting their practicality. Furthermore, the manufacturing process frequently results in excessive cement viscosity, poor fluidity, and even severe segregation and clumping. With continuous technological advancements, the requirements for materials are becoming increasingly stringent. Therefore, to address these issues, this invention provides a method for manufacturing a cement-based conductive material with low resistivity, high fluidity, stable structure, simple and efficient process, and low cost, using hydrated magnesium silicate gel as the main system. Summary of the Invention

[0003] The main objective of this invention is to address the problems existing in the prior art by inventing a method for preparing conductive materials based on a magnesium silicate graphite system. To achieve the objectives of the above invention, the present invention provides the following technical solution: A method for preparing a conductive material based on a graphitic magnesium silicate system, comprising the following components by weight: 35-45 parts of highly active magnesium oxide powder, 55-65 parts of silica fume, 45-60 parts of water (for cement), 10-60 parts of water (for graphite dispersion), 1-2 parts of water-reducing agent, 10-40 parts of graphite, and 0.1-4 parts of graphite dispersant. The production process of graphite / magnesium silicate conductive materials specifically includes the following steps: Dry mixing, preparation of dispersion solution, preparation of graphite dispersion, pulping, molding, and curing. Step (1): Dry mixing: Select a certain amount of the high-activity magnesium oxide powder and active silica and vibrate and sieve them. Mix the two sieved powders thoroughly to obtain a dry mixture. Step (2): Preparation of dispersion solution: Select a certain amount of water-reducing agent and graphite dispersant, add them to a container, add all the water (for cement + for graphite dispersant), mix thoroughly, and obtain a dispersion solution. Step (3): Preparation of graphite dispersion: Select a certain amount of graphite and add it to the dispersion solution obtained in step (2). Stir continuously for 5-10 minutes according to the Technical Conditions for Concrete Mixers (GB / T9142-1988) until the graphite is uniformly incorporated into the dispersion solution, and the graphite dispersion is obtained. Step (4): Slurry preparation: Add the dry mixture obtained in step (1) to the graphite dispersion obtained in step (3) at a speed that is fast at first and then slow. After the dry mixture is completely added and stirred evenly, continue stirring for 2-5 minutes according to the "Technical Conditions for Concrete Mixers" (GB / T9142-1988). After the graphite / magnesium silicate conductive material slurry is gradually formed evenly, stir slowly for 30-60 seconds to obtain the graphite / magnesium silicate conductive material slurry. Step (5): Molding: The graphite / magnesium silicate conductive material slurry obtained in step (4) is poured into a mold and moved to a vibration table for 30s. The mold is then moved to a curing box with a temperature of 20±2℃ and a relative humidity of >90% for 24±2h before demolding. Step (6): Curing: The demolded sample obtained in step (5) is cured in a curing chamber at a temperature of 20±2℃ and a relative humidity of >90% for 28 days to obtain a graphite / magnesium silicate conductive material. Further, during the dry mixing process in step (1), the activity of the highly active magnesium oxide powder, as measured by hydration, was not less than 65%, and its specific surface area was 24.8 m². 2 / g particle size 180-200 mesh. Further, during the dry mixing process in step (1), the active silica content in the silica fume is not less than 95%, and the specific surface area is 21.9 m². 2 / g particle size 200 mesh. In the further step (2) of preparing the dispersion solution, the graphite dispersant is sodium methylene bisnaphthalene sulfonate. Further, in the process of preparing the dispersion solution in step (2), the water-reducing agent is one of sodium hexametaphosphate, trisodium phosphate, and sodium metasilicate. Further, in the process of preparing the dispersion solution in step (2), the total water consumption is equal to the cement binding water consumption plus the graphite dispersion water consumption, and the graphite dispersion water consumption is 1-1.5 times that of graphite. In the further step (3) of preparing the graphite dispersion, the graphite is reagent grade with a specific surface area of ​​0.294 m². 2 / g, with a particle size of 800 mesh. In the further step (4) pulping process, the dry mix should be added at a fast speed first and then at a slow speed. If it is always added too fast, it will result in the inability to form a system, while if it is always added too slowly, it will result in a prolonged reaction time, which is not conducive to controlling the state of the system. Further, during the pulping process in step (4), the system will rapidly thicken during the middle of the addition of dry mix. At this time, it is only necessary to slightly shake the mixing pot or stir quickly for 10 seconds to alleviate the problem. After the dry mix is ​​completely added, the excessive viscosity will gradually disappear. In the further step (4) of the slurry preparation process, after the slurry is quickly mixed according to the "Technical Conditions for Concrete Mixers" (GB / T9142-1988), it gradually forms a uniform slurry. Then, it is slowly mixed for 30-60 seconds to remove a large number of air bubbles in the slurry. If the slow mixing process is shortened or missing, a large number of air bubbles will be present in the slurry. After the product is moved to the vibrating table in step (5), the product size will be affected, and the remaining air bubbles will seriously affect the product performance. Compared with the prior art, the features and beneficial effects of the present invention are as follows: 1. By dividing the total water consumption into cement binding water consumption and graphite dispersion water consumption, this invention can better coordinate the ratio of graphite to water during product manufacturing and reduce the excessive viscosity of the system caused by the difficulty in controlling the water absorption of graphite. 2. This invention combines the addition of graphite dispersant with the method of separately calculating the amount of water used for graphite dispersion, so that the amount of graphite that can be incorporated into the hydrated magnesium silicate system exceeds the traditional graphite percolation threshold. The amount of graphite that can be incorporated is greatly increased, so that the resistivity of the product is greatly reduced and the fluidity is excellent while ensuring mechanical properties. This method can also be applied to other easily absorbing and conductive admixtures. 3. This invention uses hydrated magnesium silicate as the main component and incorporates graphite to reduce resistivity. The system has extremely low porosity, a complete and uniform structure, and stable electrical conductivity. 4. The manufacturing method of the present invention does not require high-end equipment. Most of the operations can be completed with just an ordinary concrete mixer. The entire production process is simple, environmentally friendly and controllable. The raw materials are non-toxic, non-corrosive, inexpensive and readily available, resulting in good overall production efficiency. 5. This invention is of great significance for improving the electrical conductivity of traditional cement, expanding the application fields of cement materials, and increasing the added value and consumption of building materials. It will have a profound impact on the future development of the building materials industry. Detailed Implementation

[0004] Each component plays an indispensable and important role in the composition design of this invention. The detailed functions of each component are as follows: Magnesium silicate hydrate: As the main strength phase, it plays a major cementing role and can effectively bond graphite into the system. Its good surface gloss and low porosity can avoid the problem of excessive air content in traditional cement concrete. Its good water resistance can prevent drastic changes in resistivity after immersion in water. The overall structure is stable and the internal system is evenly distributed, which can ensure the stability of the product's conductivity. Graphite: A conductive dopant, serving as the primary conductive phase. Extensive doping provides the system with a large number of conductive particles, and when these particles are uniformly dispersed, they contribute to the system's excellent electrical properties. Graphite has a specific surface area of ​​0.294 m². 2 / g, with a particle size of 800 mesh, can be well combined with the particle size of the hydrated magnesium silicate system, thereby ensuring electrical performance while reducing the impact on other properties. Sodium methylene bis(naphthalene) sulfonate: a dispersant that plays a major role in dispersing graphite and is an anionic surfactant. It is resistant to acids, alkalis, and hard water, possesses unique dispersing and wetting power for graphite, and its aqueous solution is weakly alkaline. It has almost no impact on the formation environment of hydrated magnesium silicate, and provides good protection for colloids. It has no penetrating or foaming properties, does not affect the low porosity and surface gloss of hydrated magnesium silicate, does not affect water resistance, and ensures the stability of electrical conductivity. Water-reducing agent: one of sodium hexametaphosphate, trisodium phosphate, and sodium metasilicate, which reduces water content in cement. All three water-reducing agents can effectively complex magnesium ions in the system, delay the cement hydration reaction, prolong the setting time, facilitate the degassing operation in product production steps (4) and (5), ensure long-term plasticity, improve construction and appearance, and at the same time, will not affect the various properties of the product in the later stage. Evaluation scheme for conductive materials based on graphite / magnesium silicate system: The graphite / magnesium silicate conductive material was cast into a 40×40×40mm cubic sample, and a 28-day sample was randomly selected and ground into a 10×10×2mm cubic sample. Evaluation process Step 1, Slurry flowability test: The flowability of the sample was tested according to the "Flowability of Cement Paste" section of the "Test Method for Homogeneity of Concrete Admixtures" (GB / T8077-2012). A truncated cone mold was placed in the center of a glass plate. The well-mixed graphite / magnesium silicate conductive material slurry was quickly poured into the truncated cone mold and leveled with a scraper. The truncated cone mold was lifted vertically while a stopwatch was started. The cement paste was allowed to flow on the glass plate for 30 seconds. Then, the maximum diameter of the flowing portion in two mutually perpendicular directions was measured with a ruler, and the average of the two measurements was taken as the flowability of the cement paste. Step 2: Compressive strength test The compressive strength of 40×40×40mm cube specimens aged 3d, 7d, 14d, and 28d was tested using a YDE-300D universal testing press at a loading rate of 2.4kN / s. Five specimens were taken from each group, and the average value of the compressive strength results was taken. Step 3, resistivity test: The resistivity of 10×10×2mm cubic specimens aged 28 days was tested using a Swin HALL8800 Hall effect tester. Three specimens were taken from each group, and the average value of the resistivity test results was taken. The present invention will be described in detail below with reference to the embodiments, but the scope of the present invention is not limited to the following embodiments. Within the compositional range of this invention, samples with graphite content of 15% and 30% were taken as Example 1 and Example 2, respectively. Additionally, a sample without graphite and dispersant was designated as Comparative Example 1; a sample with 15% graphite content and no graphite dispersant was designated as Comparative Example 2; and a sample with 15% graphite content and hydroxypropyl methylcellulose as a dispersant was designated as Comparative Example 3. Example 1: The raw material composition is as follows: 400g of highly active magnesium oxide powder, 600g of silica fume, 695g of deionized water, 20g of sodium hexametaphosphate, 150g of graphite, and 5g of sodium methylene bisnaphthalene sulfonate. The preparation process is as follows: Select highly active magnesium oxide powder and vibrate it through a 180-mesh sieve. Select silica fume and vibrate it through a 200-mesh sieve. Weigh 400g of the sieved highly active magnesium oxide powder and 600g of the sieved silica fume, and pour them into a cement mixing pot. Start slow stirring until the highly active magnesium oxide powder and silica fume in the pot are fully mixed. Remove all the dry mixture and set it aside. Weigh 20g of sodium hexametaphosphate and 5g of sodium methylene bis(naphthalene) sulfonate and pour them into the cement mixing pot. Weigh 695g of deionized water and pour it into the cement mixing pot. Start slow stirring for 20 minutes until the sodium hexametaphosphate and sodium methylene bis(naphthalene) sulfonate are fully dissolved. Weigh 150g of graphite and pour it into the mixing pot. Cover the mixing pot with plastic sheeting and start slow stirring for 4-8 minutes until the graphite on the surface of the solution is completely incorporated into the dispersion. Use a scraper to scrape off the graphite powder from the plastic sheeting, the bottom of the mixing pot, and the walls of the mixing pot. Start slow stirring for 1-2 minutes until all the graphite in the pot is uniformly incorporated, thus obtaining the graphite dispersion. Turn on the mixing bowl and stir slowly. Cover the mixing bowl with a plastic sheet. While stirring slowly, pour the dry mixture into the mixing bowl along the side of the bowl at a decreasing speed, starting fast and then slowing down. If the mixture becomes too thick, tap the side of the bowl with a mallet for 10 seconds or turn on fast stirring for 10 seconds to restore its consistency. Control the pouring time of the dry mixture to within 2-3 minutes. After the dry mixture has been completely poured in, scrape it off the stirring rod, the bottom of the mixing bowl, the sides of the bowl, and the plastic sheet with a scraper. Stir slowly for 10 seconds, then turn on fast stirring for 2 minutes. Once the slurry has gradually formed, turn on slow stirring for 30 seconds to obtain the graphite / magnesium silicate conductive material slurry. Take a small amount of the graphite / magnesium silicate conductive material slurry for a flowability test. Most of the graphite / magnesium silicate conductive material slurry was poured into a 40×40×40mm cubic sample mold. The mold was moved to a vibration table and vibrated for 30 seconds. Excess slurry was scraped off the mold with a scraper. The mold was then placed in a constant temperature and humidity curing chamber at 20±2℃ and relative humidity >90% for 24±2 hours. After the sample was demolded, it was cured in a constant temperature and humidity curing chamber at 20±2℃ and relative humidity >90% for 28 days to obtain the graphite / magnesium silicate conductive material sample. Step 1, Slurry flowability test: Wipe the glass plate and the truncated cone mold with a damp cloth, ensuring they are moist but without water stains. Place the truncated cone mold in the center of the glass plate. Quickly pour the well-stirred graphite / magnesium silicate conductive material slurry into the truncated cone mold and smooth it with a scraper. While lifting the truncated cone mold vertically, start a stopwatch and allow the cement slurry to flow on the glass plate for 30 seconds. Then, use a ruler to measure the maximum diameter of the flowing part in two mutually perpendicular directions and take the average of the two measurements as the fluidity of the cement slurry. Step 2: Compressive strength test The compressive strength of 40×40×40mm cube specimens aged 3d, 7d, 14d, and 28d was tested using a universal testing machine of model YDE-300D at a loading rate of 2.4kN / s. Five specimens were taken from each group, and the average value of the results was used as the compressive strength value to evaluate the compressive performance. The results are shown in Table 1. Step 3, resistivity test: The 28-day-old samples were sanded to a cube of 10×10×2mm. The resistivity of the 10×10×2mm cube samples was tested using a SwinHALL8800 Hall effect tester. Three samples were taken from each group. The average resistivity test result was taken as the resistivity value of the sample at 28 days to evaluate its performance. The results are shown in Table 1. Example 2: The raw material composition is as follows: 400g of highly active magnesium oxide powder, 600g of silica fume, 890g of deionized water, 20g of sodium hexametaphosphate, 300g of graphite, and 10g of sodium methylene bisnaphthalene sulfonate. The preparation method in this embodiment is the same as in Example 1, except that the amount of graphite is 300g and the amount of deionized water is 890g. The sample evaluation process in this embodiment is the same as in Embodiment 1. Comparative Example 1: The raw material composition is: 400g of highly active magnesium oxide powder, 600g of silica fume, 500g of deionized water, and 20g of sodium hexametaphosphate. The preparation process is as follows: Select highly active magnesium oxide powder and vibrate it through a 180-mesh sieve. Select silica fume and vibrate it through a 200-mesh sieve. Weigh 400g of the sieved highly active magnesium oxide powder and 600g of the sieved silica fume, and pour them into a cement mixing pot. Start slow stirring until the highly active magnesium oxide powder and silica fume in the pot are fully mixed. Remove all the dry mixture and set it aside. Weigh 20g of sodium hexametaphosphate and pour it into the cement mixing pot. Weigh 500g of deionized water and pour it into the cement mixing pot. Start slow stirring for 20 minutes until the sodium hexametaphosphate is fully dissolved. Turn on the mixing bowl and stir slowly. Cover the mixing bowl with a plastic sheet. While stirring slowly, pour the dry mixture into the mixing bowl along the side of the bowl at a gradually decreasing speed, controlling the pouring time to be within 2-3 minutes. After the dry mixture has been completely poured in, use a spatula to scrape off the dry mixture from the stirring rod, the bottom of the mixing bowl, the sides of the bowl, and the plastic sheet. Stir slowly for 10 seconds, then increase the speed to stir for 2 minutes. Once the slurry has gradually formed, stir slowly for 30 seconds to obtain the slurry of Comparative Example 1. Take a small amount of the slurry for a flowability test. Most of the slurry was poured into a 40×40×40mm cubic sample mold. The mold was moved to a vibrating table and vibrated for 30 seconds. Excess slurry was scraped off the mold with a scraper. The mold was then placed in a constant temperature and humidity curing chamber at 20±2℃ and relative humidity >90% for 24±2 hours. The sample was then demolded and cured in a constant temperature and humidity curing chamber at 20±2℃ and relative humidity >90% for 28 days to obtain the sample of Comparative Example 1. The evaluation process for this comparative sample is the same as in Example 1. Comparative Example 2: The raw material composition is as follows: 400g of highly active magnesium oxide powder, 600g of silica fume, 1250g of deionized water, 20g of sodium hexametaphosphate, and 150g of graphite. The preparation method of this comparative example is the same as that of Example 1, except that sodium methylene bis(naphthalene)sulfonate was not added and the amount of deionized water used was 1250g. The evaluation process for this comparative sample is the same as in Example 1. Comparative Example 3: The raw material composition is as follows: 400g of highly active magnesium oxide powder, 600g of silica fume, 800g of deionized water, 20g of sodium hexametaphosphate, 150g of graphite, and 5g of hydroxypropyl methylcellulose. The preparation method of this comparative example is the same as that of Example 1, except that hydroxypropyl methylcellulose is used instead of sodium methylene bisnaphthalene sulfonate and 800g of deionized water is used. The evaluation process for this comparative sample is the same as in Example 1. Table 1. Performance test results of samples from Examples 1-2 and Comparative Examples 1-3. As shown in the table above, the graphite / magnesium silicate conductive material containing the graphite dispersant of this invention exhibits the following properties: at a graphite content of 15%, the 28-day compressive strength reaches 24.5 MPa with a strength retention coefficient of 0.81, the resistivity reaches 3.15 × 10 Ω·cm (a decrease of 54.9%), and the flowability reaches 204 mm; at a graphite content of 30%, the 28-day compressive strength reaches 14.9 MPa with a strength retention coefficient of 0.49, the resistivity reaches 1.37 × 10 Ω·cm (a decrease of 80.3%), and the flowability reaches 202 mm. This invention relates to a graphite / magnesium silicate conductive material, prepared by incorporating graphite as a conductive admixture into a hydrated magnesium silicate gel system. By adding sodium methylene bis(naphthalene)sulfonate dispersant and separately calculating the water requirement for graphite dispersion, the graphite content in the magnesium silicate system exceeds the percolation threshold. This significantly reduces the resistivity of the product while maintaining a certain strength. Furthermore, the product exhibits excellent flowability, structural stability, and a simple, efficient, environmentally friendly, and low-cost process. This invention is of great significance for preparing cement-based conductive materials, improving the conductivity of magnesium silicate cement, enhancing the practicality of hydrated magnesium silicate cement, increasing the added value of building materials, and promoting the future development of the building materials industry.

[0005] Unless otherwise specified, the raw materials and experimental equipment used in this invention are commonly used in the field; the experimental methods used in this invention are conventional experimental methods in the field.

[0006] The above embodiments are only some embodiments of the present invention and do not limit the present invention in any way. Any simple modifications, changes and equivalent transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a graphite / magnesium silicate conductive material, characterized in that, Prepare the following components by weight: 35-45 parts high-activity magnesium oxide powder, 55-65 parts silica fume, 45-60 parts cement water, 10-60 parts graphite dispersion water, 1-2 parts water-reducing agent, 10-40 parts graphite, and 0.1-4 parts graphite dispersant. The preparation method of the graphite / magnesium silicate conductive material specifically includes the following steps: Step (1): Dry mixing: Select a certain amount of the high-activity magnesium oxide powder and silica fume and vibrate and sieve them. Mix the two sieved powders thoroughly to obtain a dry mixture. Step (2): Preparation of dispersion solution: Select a certain amount of water-reducing agent and graphite dispersant and add them to a container. Add all the water, including cement water and graphite dispersion water. Mix thoroughly to obtain a dispersion solution. Step (3): Preparation of graphite dispersion: Select a certain amount of graphite and add it to the dispersion solution obtained in step (2). Stir continuously for 5-10 minutes according to GB / T9142-1988 "Technical Conditions for Concrete Mixers" until the graphite is uniformly incorporated into the dispersion solution, and the graphite dispersion is obtained. Step (4): Slurry preparation: Add the dry mixture obtained in step (1) to the graphite dispersion obtained in step (3) at a speed that is fast at first and then slow. After the dry mixture is completely added and stirred evenly, continue stirring for 2-5 minutes according to GB / T9142-1988 "Technical Conditions for Concrete Mixers". After the graphite / magnesium silicate conductive material slurry is gradually formed evenly, stir slowly for 30-60 seconds to obtain the graphite / magnesium silicate conductive material slurry. Step (5): Molding: The graphite / magnesium silicate conductive material slurry obtained in step (4) is poured into a mold and moved to a vibration table for 30s. The mold is then moved to a curing box with a temperature of 20±2℃ and a relative humidity of >90% for 24±2h before demolding. Step (6): Curing: The demolded sample obtained in step (5) is cured in a curing chamber at a temperature of 20±2℃ and a relative humidity of >90% for 28 days to obtain a graphite / magnesium silicate conductive material. In step (2), during the preparation of the dispersion solution, the water requirement for cement bonding and the water requirement for graphite dispersion are calculated separately. The method for calculating the water requirement for graphite dispersion is that the mass ratio of graphite to distilled water is 1:1-1.

5. In step (2), the graphite dispersant used in the preparation of the dispersion solution is sodium methylene bisnaphthalene sulfonate.

2. The method for preparing a graphite / magnesium silicate conductive material according to claim 1, characterized in that, During the dry mixing process in step (1), the activity of the highly active magnesium oxide powder, as measured by the hydration method, was not less than 65%, and its specific surface area was 24.8 m². 2 / g, particle size 180-200 mesh; During the dry mixing process in step (1), the active silica content in the silica fume is not less than 95%, and the specific surface area is 21.9 m². 2 / g, particle size 200 mesh.

3. The method for preparing a graphite / magnesium silicate conductive material according to claim 1, characterized in that, In step (2), during the preparation of the dispersion solution, the water-reducing agent is one of sodium hexametaphosphate, trisodium phosphate, or sodium metasilicate.

4. The method for preparing a graphite / magnesium silicate conductive material according to claim 1, characterized in that, In step (3), during the preparation of the graphite dispersion, the graphite is reagent grade with a specific surface area of ​​0.294 m². 2 / g, with a particle size of 800 mesh.

5. The method for preparing a graphite / magnesium silicate conductive material according to claim 1, characterized in that, In step (4) of the pulping process, the system will become rapidly thickened in the middle of the addition of dry mix. At this time, it can be relieved by simply shaking the mixing pot slightly or stirring quickly for 10 seconds. The excessive viscosity will gradually disappear after the dry mix is ​​completely added.

Citation Information

Patent Citations

  • A kind of conductive cement mixed with low melting point alloy and its preparation method

    CN105801076B

  • Conductive super high ductility cement-based composite material and preparation method thereof

    CN109626908A

  • A kind of high-strength and high-conductivity concrete and preparation method thereof

    CN116354672B

  • A self-compacting conductive concrete

    CN116409974B

  • Corrosion-resistant high-strength conductive concrete and preparation method thereof

    CN102432239A